2005
DOI: 10.1007/s10194-005-0166-1
|View full text |Cite
|
Sign up to set email alerts
|

Nosology and treatment of primary headache in a Swiss headache clinic

Abstract: We assessed demographics, diagnoses, course, severity, impact and treatment of primary headache outpatients from records in the Headache and Pain Clinic, Neurological Department, Zürich University Hospital. All outpatients seen from 1996 to 1998 for migraine, tension–type headache, and both, were included. Diagnoses, drug, physical and alternative treatments before and after referral were listed. Descriptive statistics were used for differences between the general population and this sample, the diagnoses, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 9 publications
1
20
0
3
Order By: Relevance
“…We used the AMC in a headache clinic that has a higher rate and severity of migraine headache compared to primary care centers. 12 The number of patients in our study who contributed to groups other than true-positive was small, and this has probably affected the NPV and PPV, which are critically dependent on the prevalence of the disorder in the sample. Because of these limitations, the validity of the NPV and PPV should be confined to the patient population of tertiary headache centers.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We used the AMC in a headache clinic that has a higher rate and severity of migraine headache compared to primary care centers. 12 The number of patients in our study who contributed to groups other than true-positive was small, and this has probably affected the NPV and PPV, which are critically dependent on the prevalence of the disorder in the sample. Because of these limitations, the validity of the NPV and PPV should be confined to the patient population of tertiary headache centers.…”
Section: Discussionmentioning
confidence: 96%
“…13 The ICHD-I had a sensitivity of 27.3% and a specificity of 92.4% for migraine diagnosis, 13 and these poor results for childhood migraine result from the rarity of certain migraine features in children. 12 Senbil et al compared the ICHD-II, as the gold standard, with the clinical diagnoses of a pediatric neurologist, and found that the ICHD-II had 90.3% specificity, 78.7% sensitivity and a high validity for the diagnosis of migraine. 14 In another study of children and adolescents, the ICHD-II had a sensitivity of 53% and 71% for migraine without, and with, aura compared to the clinical diagnosis of experts as gold standard.…”
Section: Discussionmentioning
confidence: 98%
“…However, little is known about the patterns of CAM use in adults with migraines. Only a few prior surveys have examined CAM use in patients with headaches, and most were conducted in outpatient headache centers with small samples 5,9‐14 . Knowing the prevalence and patterns of use of CAM in adults with migraines will help to characterize areas of potential underuse and barriers to use, as well as potential risks of CAM therapies in adults with migraines.…”
mentioning
confidence: 99%
“…Nonetheless, in a study conducted in the United Kingdom, Kernick et al reported that 70% of patients presenting to GPs with new-onset primary headaches did not receive a diagnosis [3], which might be due to the fact that primary healthcare often deals with early undifferentiated stages of illnesses. An earlier study in a Swiss tertiary care centre revealed a similarly high number of incorrect or unspecified diagnoses [9]. The clinical problem of headache demands appropriate medical attention, and it seems that the cooperation between primary care physicians and headache specialists still needs to be improved.…”
Section: Discussionmentioning
confidence: 99%